Wnt7a Interaction with Fzd5 and Detection of Signaling Activation Using a Split eGFP - Carmon, Kendra S. (2008)
Wnts are secreted glycoproteins that regulate important cellular processes including proliferation, diiferentiation, and cell fate. In the β-catenin/canonical pathway, Wnt interacts with Fzd receptors to inhibit degradation of β-catenin and promote its translocation into the nucleus where it regulates transcription of a number of genes. Dysregulation of this pathway has been attributed to a host of diseases including cancer. As a result, components of the β-catenin/canonical pathway have been gaining recognition as promising targets for the discovery of novel therapeutic agents. Here we show, using an ELISA-based protein-protein binding assay that purified Wnt7a binds to the extracellular cysteine-rich domain of Fzd5 in the nanomolar range. We have developed a novel split eGFP complementation assay to visually detect Wnt7a-Fzd5 interactions and subsequent pathway activation in cells. These biological tools could help lead to a better understanding of Wnt-Fzd interactions and the identification of new modulators of Wnt signaling.